ADVANCED RISK FINANCE - Greenhill, James P. (Assurances)

(untitled) (HEC Montréal, 2000)
In this paper we will look at a number of typical cases in order to introduce some Advanced Risk Financing (ARF) concepts. This includes a review of the evolution of ARF products from early techniques, where ARF practitioners are interested in alternative ways of funding traditional risk exposures, to the latest more sophisticated products, where corporations seek to achieve efficiencies through holistic risk financing approaches. We will discuss how, within the past few years, insurance and other financial techniques have converged, allowing insurance markets to assume risks that are normally laid off in the derivative or capital markets. Finally, we will discuss when and where these advanced applications make sense.